PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT MINA ABADI MEKANIKA KEBAYORAN BARU JAKARTA SELATAN - Lisani Asya Fatin; Retno Japanis Permatasari (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect between training variables on employee performance, to determine the effect of work discipline variables on employee performance and to determine the effect of training variables and work discipline simultaneously on employee performance at PT Mina Abadi Mekanika Kebayoran Baru South Jakarta. The sample used is a saturated sample technique totaling 60 employees. Data collection techniques through primary and secondary data. The method used is quantitative with an associative approach. The results showed that Training (X1) is zero or does not increase, then Employee Performance (Y) will Keywords: Training, Work Discipline, Employee Performance remain at 6,130. The regression coefficient is 0.413, which shows a unidirectional effect, meaning that every one-unit increase in the training variable will increase performance by 0.413. The t test has a calculated t value of 2.012 and a 5% distribution table value of 2.002, then t count 2.012> t table 2.002 with a sig level. <0.05, namely 0.000. Work Discipline (X2) is zero or does not increase, then Employee Performance (Y) will remain at 8.141. The regression coefficient is 0.805, which shows a unidirectional effect, meaning that every increase in Work Discipline by one unit will increase performance by 0.805. The t test has a t value of 10.587 and a 5% distribution table value of 2.002, then t count 10.587> t table 2.002 with a sig level. <0.05 which is 0.000